Evaluation of cerebral venous thrombosis by computed tomography/MRI and magnetic resonance venography in pregnant and postpartum women: a prospective study - Singh, Neelam; Udainiya, Dinesh; Kulshreshtha, Sonal; Bindal, Jyoti (International Journal of Research in Medical Sciences, 2018)
Background: Diagnosis of Cerebral venous thrombosis (CVT) is challenging as it is an uncommon cause of stroke with varied clinical presentations, predisposing factors, imaging findings, and outcomes. Prompt and accurate diagnosis is important for timely intervention in order to reverse and significantly reduce the acute and long-term sequel. Aims and objectives was to study cerebral venous thrombosis in pregnant and post-partum women. Methods: Hundred pregnant and postpartum women having CVT were studied at Kamla Raja Hospital and JA Group of Hospital at GR Medical College, Gwalior Madhya Pradesh for study period of 2016 to 2017. All the women had undergone CT/MRI and MRV. Results: Age of CVT patients ranged from 18-35 years with a maximum incidence (84%) in the 2nd decade (20-30 years). Sixty two percent women had infarction; out of that 53% had hemorrhagic infarction. Frontal lobe (10%) and temporal lobe (10%) were more affected. Superior sagittal sinus (SSS) was most commonly involved (71%) followed by transverse sinus (66%) and sigmoid sinus (45%). Superficial venous system was involved in 32 patients while deep venous system was involved in 20 patients. Majority of (82%) patients had combination of sinuses and venous involvement. Conclusions: CVT was more prevalent in young pregnant and postpartum women. Hemorrhagic infarction were common and affecting frontal and temporal lobe. SSS were mostly affected in CVT. MRV should be the first line diagnostic tool for diagnosis of CVT in pregnant and postpartum women.